Learning Cython Programming - Herron, Philip (Packt Publishing, 2013)
Cython is a very powerful combination of Python and C. Using Cython, you can write Python code that calls back and forth from and to C or C++ code natively at any point. It is a language with extra syntax allowing for optional static type declarations. It is also a very popular language as it can be used for multicore programming. This book will provide you with a detailed guide to extending your native applications in pure Python; imagine embedding a twisted web server into your native application with pure Python code. You will also learn how to get your new applications up and running by reusing Pythons extensive libraries such as Logging and Config Parser to name a few.